2020
DOI: 10.1111/and.13732
|View full text |Cite
|
Sign up to set email alerts
|

Swim‐up as a strategy for isolation of spermatozoa without viral incorporation in men with chronic hepatitis B: A pilot study

Abstract: Hepatitis B is a viral infectious disease caused by the hepatitis B virus (HBV). According to the World Health Organization (WHO), worldwide 257 million people are chronically infected with HBV in 2015 WHO 2018. The prevalence of chronic hepatitis B (cHB), defined as Hepatitis B surface Antigen (HBsAg) seropositivity, varies between different WHO regions, from 0.7% in the American Region to 6.1% in the African Region and 6.2% in the Western Pacific Region. In the WHO European Region, prevalence is estimated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Therefore, the Belgian–Dutch Association for Artificial Insemination advises against ICSI treatment for chronic patients with HBV [ 50 ]. Condijts et al [ 198 ] suggested that strategies to select sperm cells without HBV incorporation are necessary to avoid excluding chronically infected men.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Belgian–Dutch Association for Artificial Insemination advises against ICSI treatment for chronic patients with HBV [ 50 ]. Condijts et al [ 198 ] suggested that strategies to select sperm cells without HBV incorporation are necessary to avoid excluding chronically infected men.…”
Section: Discussionmentioning
confidence: 99%